Ecolinguistic: State of The Art Phonological Anapticsis of Javanese Lamongan and Kediri Dialect - Farian Dito Irwanda; Thoriqi Firdaus (Winaya Inspirasi Nusantara Foundation, 2024)
The Javanese language in the East Java province exhibits diverse dialects, such as the Kediri (Mataraman) dialect and the Lamongan (Arekan) dialect, which are geographically proximate. The goal of this study is to describe the different ways that phonological sounds change when the Javanese language is spoken, as well as the different ways that anaphoric sounds change when vowel and consonant phonemes are added, such as prosthesis, epenthesis, and paragoge. The research employs a qualitative descriptive method with an ecolinguistic approach. Interviews are used for data collection and acquisition, followed by note-taking and recording as the primary data reference. The analysis results reveal 33 differences in the phonological usage of the Javanese language between the Kediri (Mataraman) dialect and the Lamongan (Arekan) dialect. The classification of anaptyctic sound changes is distinctly evident in the use of the Javanese language. The dialects, in their daily usage, demonstrate two instances of change via prosthesis, two instances via epenthesis, and three instances via paragoge. The analysis identifies ecolinguistic factors influencing the phonological changes between these two dialects. Phonological changes occur as a result of contact with other languages or dialects, population migration, and social changes within the local community. The ecolinguistic study of anaptyctic phonological changes between the Lamongan and Kediri dialects indicates the influence of geographical, environmental, social interaction, and cultural factors.